Programmers’ affinity to languages - Neto, Álvaro (2021)
Students face several challenges when learning computer programming languages, a central topic to acquire programming skills. While those challenges that present a predominantly technical nature have been intensely studied by researchers along the years, the ones that are concerned with qualitative, and personal aspects have not. Affinity to a programming language is one of the many personal factors that may contribute to surpass these qualitative aspects that describe the difficulties that students face. From this point-of-view, this paper presents a proposal for treating and studying programmers’ affinity to programming languages as an important factor for learning computer programming. It also reports a preliminary questionnaire conducted on a master’s degree class at Universidade do Minho that showed that affinity may have a broader relation to learning computer programming than anticipated. Finally, a set of relevant questions are stated to compose a future inquiry aimed at deepening the knowledge on the affinity between programmers and languages, paving the way for following research.